Left Bundle Branch Area Pacing vs. Biventricular Pacing for Cardiac Resynchronization Therapy: A Meta-Analysis - Liu, Jiyi; Sun, Fengzhi; Wang, Zefeng; Sun, Jiao; Jiang, Xue; Zhao, Weilong; Zhang, Zhipeng; Liu, Lu; Zhang, Shulong (Frontiers in Cardiovascular Medicine, 2021)
Background: Left bundle branch area pacing (LBBAP) is a recently proposed method for conduction system pacing. We performed a meta-analysis of controlled studies to compare the clinical outcome in patients who received LBBAP vs. biventricular pacing (BVP) for cardiac resynchronization therapy (CRT). Methods: PubMed, Embase, and Cochrane's Library databases were searched for relevant controlled studies. A random-effect model incorporating the potential heterogeneity was used to synthesize the results. Results: Four non-randomized controlled studies including 249 patients with heart failure (HF) for CRT were included, and the patients were followed for 6–12 months. Compared with BVP, LBBAP was associated with significantly shortened QRS duration [mean difference (MD): −29.18 ms, 95% confidence interval (CI): −33.55–24.80, I2 = 0%, P < 0.001], improved left ventricular ejection fraction (MD: 6.93%, 95% CI: 4.69–9.17, I2 = 0%, P < 0.001), reduced left ventricular end-diastolic dimension (MD: −2.96 mm, 95% CI: −5.48 to −0.44, I2 = 0%, P = 0.02), and improved New York Heart Association class (MD: −0.54, 95% CI: −0.84 to −0.24, I2 = 65%, P < 0.001). Moreover, patients who received LBBAP were more likely to achieve echocardiographic [odds ratio (OR): 5.04, 95% CI: 2.17–11.69, I2 = 0%, P < 0.001] and clinical (OR: 7.33, 95% CI: 1.62–33.16, I2 = 0%, P = 0.01) CRT responses. Conclusion: Current evidence from non-randomized studies suggests that LBBAP appears to be a promising method for CRT, which is associated with more remarkable improvements of symptoms and cardiac function in HF patients with indication for CRT.